Assessment of heavy metals contamination of agricultural soils using pollution indicators in Thi-Qar governorate, Southern Iraq - Ahmed, Amal; Saher Abdulridha Ali (University of Thi-Qar Journal of Science, 2023)
This study aims to assess the levels of contamination of agricultural soils with heavy elements (cobalt, copper, iron, nickel, cadmium, and lead) in three regions in Thi-Qar Governorate, Southern Iraq. These three regions are Al-Gharraf, Al-Islah, and Al-Batha. The study was done by using the pollution indicators, which are geographical pollution index (Igeo), contamination degree (Cd), contamination factor (Cf), pollution load index (PLI), potential ecological risk factor (Er), and finally, risk index (RI). From each region, four soil samples were collected from holes 25 cm deep, separated by a distance of 500 meters. After the digestion process of the samples, the concentrations of the studied elements were measured by flam atomic absorption spectrometer (FAAS). The results showed that the average heavy metal concentrations for all samples were (365.810, 96.424, 41.36, 11.919, 5.194 and 0.352 mg/kg). They were in the following order Fe > Ni > Cu >Co > Pb > Cd, respectively. The concentrations of heavy metals in the study areas were all within the limits allowed by the World Health Organization (WHO) except for 8.3% of the studied areas that were beyond the permissible limits for cadmium only. The reason for the increase in cadmium concentrations in some areas could be due to sewage, industrial emissions and agricultural practices. According to the Igeo values, the levels of minerals studied for the three regions followed the following order Cd > Cu > Co > Pb > N i> Fe.